Subjective evaluation of visual acuity is not reliable to detect disease activity in different exudative maculopathies - Bründer, Marie-Christine; Benjamin, Nicola (Graefe's archive for clinical and experimental ophthalmology, 2018)
Background: Patients with exudative maculopathies (neovascular age-related macular degeneration (nAMD), diabetic macular edema (DME), and retinal vein occlusion (RVO)) are faced with a high burden of examinations and treatments. This study was conceived to analyze the accuracy of a subjective evaluation of visual acuity (VA) and metamorphopsia to detect disease reactivation, compared to morphological signs of reactivation assessed by means of SD-OCT. Methods: Retrospective study of 888 patients treated for nAMD (n = 638), DME (84), BRVO (110), and CRVO (56) was conducted. Subjective evaluation of the patient at an examination (i.e., change of VA and/or metamorphopsia) was compared to clinical evaluation of disease activity as assessed by SD-OCT. Sensitivity and specificity, negative and positive predictive values (PPV/NPV) for detection of active disease were calculated. Factors associated with false-negative subjective evaluation were analyzed by regression analysis. Results: The sensitivity of the subjective evaluation to detect disease reactivation was < 0.50 in all exudative maculopathies. Sensitivity was increased to ≥ 0.60 by combining subjective worsening with loss of 1 line in the VA test in RVO, but not in DME and nAMD. The specificity was > 0.85 in all patients. PPV was > 0.85 in patients with RVO. Regression analysis did not reveal any factors that could reliably identify patient subgroups in which OCT could be omitted, though CRVO patients with a visual acuity of < 0.3 logMAR had an odds ratio of 0.20 for false-negative subjective evaluation (p = 0.009). Conclusion: The accuracy of subjective evaluation to discriminate disease activity in patients with different exudative maculopathies was low and cannot substitute for frequent SD-OCT exams. Routinely assessed clinical parameters such as age, visual acuity, or treatment experience were of no use to predict the validity of subjective evaluation of disease activity. Trial registration: This trial was registered at the DRKS (Deutsches Register Klinischer Studien, drks.de; No 00006851) prior to the inclusion of the first patient.